HUBUNGAN TIPE KEPRIBADIAN DAN HEALTH LOCUS OF CONTROL TERHADAP TINGKAT KEPATUHAN BEROBAT PENDERITA TB PARU - Lestari, Seruni (Coping: Community of Publishing in Nursing; Vol 2 No 2 (2014): JURNAL EDISI MEI-AGUSTUS 2014, 2014)
Normal 0 false false false EN-US X-NONE X-NONE Tuberculosis (TB) is an infectious disease, which primarily affects the lung parenchym . TB not only attacks the lungs but can affect other organs, including the meningen, kidneys, bones and lymph nodes. Major infectious agent of this disease is mycobacterium tuberculosis that is resistant to acid aerobic rods that grow slowly and are sensitive to heat and ultraviolet light. This research was an descriptive correlation study with cross sectional design. 38 respondent was collected by purposive sampling at Sanglah Hospital. The test are used were chi square and logistic regression (p value <?, ? = 0.05). The results showed that there was a significant relationship between personality type (p value = 0.000, OR = 29,902, CI = 3,191-280,175 ), health locus of control (p value = 0.016, OR = 18,616, CI = 1,456-238,078 ) with the level of treatment adherence. Research conclusion, personality type and health locus of control had effect on the level compliance of TB patient. Required a nurse’s communication skill to chance health locus of control to positif to motivate patients with pulmonary tuberculosis to do the treatment regularly /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; text-align:justify; text-indent:.5in; line-height:200%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin;}
Keywords: personality type, health locus of control, the level of compliance.